Family characters related to malnutrition among preschool children - Cajilo, Ma. Donna
This is co-relational study of family characteristics related to malnutrition among preschool children. It aimed to : 1) find out if there is a relationship between family size and malnutrition among preschool children, 2) find out if there is a relationship between birth spacing and malnutrition among preschool children, and 3.) find out if there is a relationship between mother's work and malnutrition among preschool children. The study used interview guide to gather data. It utilizes materials from books, journals and magazines. There were 30 respondents. These were the mothers of the identified 2nd and 3rd degree malnourished preschool children of Barangay Pitogo, San Joaquin, Iloilo. The researcher utilized the entire population of the mothers of the identified 2nd and 3rd degree malnourished preschool children because there were 30 only. The researcher didn't include the mothers of the 1st degree malnourished preschool children due to fact that nutritional status of the child easily shifts to normal condition, therefore, data gathered maybe true for a short period of time and is not reliable for further study. The data was analyzed using frequency counts, percentages and the chi-square test for independence. The study found out that : 1) there is no significant relationship between family size and malnutrition among preschool children, 2) There is no significant relationship between birth spacing and malnutrition among preschool children, and 3.) there is no significant relationship between mother's work and malnutrition among preschool children.